2018
DOI: 10.1111/imm.12880
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic and peripheral blood phenotypes of natural killer and T cells: differential surface expression of killer cell immunoglobulin‐like receptors

Abstract: Deep characterization of the frequencies, phenotypes and functionalities of liver and peripheral blood natural killer (NK), natural killer T (NKT) and T cells from healthy individuals is an essential step to further interpret changes in liver diseases. These data indicate that CCR7, a chemokine essential for cell migration through lymphoid organs, is almost absent in liver NK and T cells. CD56 NK cells, which represent half of liver NK cells, showed lower expression of the inhibitory molecule NKG2A and an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
(64 reference statements)
1
6
0
Order By: Relevance
“…Initial characterization of hepatic NK cells in our study cohort showed that NK cells were enriched in the liver, predominantly comprising CD56 Bright NK cells with lower CD16 expression. Comparable observations have been made by several other groups indicating that the composition of hepatic NK cells of our study cohort can be considered representative . Assessment of the residency markers CD49a and CXCR6 showed increased frequency in hepatic lymphocytes but also a differential expression between these markers on lymphocytes and NK cells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Initial characterization of hepatic NK cells in our study cohort showed that NK cells were enriched in the liver, predominantly comprising CD56 Bright NK cells with lower CD16 expression. Comparable observations have been made by several other groups indicating that the composition of hepatic NK cells of our study cohort can be considered representative . Assessment of the residency markers CD49a and CXCR6 showed increased frequency in hepatic lymphocytes but also a differential expression between these markers on lymphocytes and NK cells.…”
Section: Discussionsupporting
confidence: 85%
“…Comparable observations have been made by several other groups indicating that the composition of hepatic NK cells of our study cohort can be considered representative. 23,25,39 Assessment of the residency markers CD49a and CXCR6 showed increased frequency in hepatic lymphocytes but also a differential expression between these markers on lymphocytes and NK cells. CD49a was predominantly expressed by non-NK lymphocytes, whereas NK cells did not express CD49a to a significant degree similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%
“… 90 , 92 In the human liver, NK cells account for 50% of the total lymphocyte count and comprise hepatic CD56 bright CCR5 + CXCR6 + CD69 + trNKs, transient cNKs, and memory-like NKs. 94 , 95 This high percentage itself shows the extent of their contribution towards detoxification, which is undoubtedly one of the major functions of the liver. Moreover, they promote hepatic tolerance and homeostasis by interacting with hepatocyte HLA-E through the NKG2A inhibitory receptor to prime DCs via the release of TGF-β, eventually resulting in the expansion of CD4 + CD25 + T reg cells.…”
Section: Human Nk Cells In Distinct Tissue Compartmentsmentioning
confidence: 99%
“…5,7 In particular, the hepatic T-cell population includes more activated and terminally differentiated cells than the PB T-cell population. [8][9][10] In addition, compared to the PB, the liver population is enriched with CD8 + T cells expressing receptors that are typically expressed by NK cells. 11,12 For example, CD8 + T cells expressing killer immunoglobulin-like receptors (KIRs) or NKG2A are more prevalent in the liver than the PB.…”
Section: Introductionmentioning
confidence: 99%